Critical Benefitial Aspects of Total Quality Management- The Case of Kombolcha Textile Share Company, Ethiopia - Sandeep Kumar Gupta, Yimer Ayalew, Vivek Srivastava, Chris Egbu, Leena Kumari, Amare AY (International Journal of Advanced Science and Technology, 2020)
It has been seen that due to globalization, technological changes and changing customer’s needs and demands for better quality, Kombolcha textile manufacturing Share Companyis facing severe competition by abroad textile businesses. In this dynamic business competition, customers never compromise on quality matters being it is one key strategic factor. However, to achieve high organizational performance, successful implementation of Total Quality Management benefits aspects is one of the peak advantage ousrequirements.The objective of this research has to investigate the effect of total quality management critical success factors customer focus, top management commitment, employee fulfilment, continuous improvement and organizational learning on organizational performance. The research design was explorative and quantitative data obtained using rating scale questionnaire from 181 managerial, professional and junior professional employees of the organization, and qualitative data from journals and books. Stratified and systematic sampling techniques have been adopted for the research. With the help of SPSS 16.0 program was used for data reliability, validity, correlation, Standard Multiple Regression analysis. The results of the analysis revealed that there were positive and significant effects of TQMCSFs on organizational performance. Hence, the company may adopt TQMCSFs to boost Organizational Performance.